2020
DOI: 10.1108/he-09-2019-0040
|View full text |Cite
|
Sign up to set email alerts
|

Food and cultural norms: rural mothers' selection of nutrition intake for their young children

Abstract: PurposeThis study aimed at exploring food related cultural norms that influence rural mothers' food selection for their primary school aged children (aged 4–7 years).Design/methodology/approachThis is a qualitative study conducted in northern parts of Balochistan province of Pakistan. The Theory of Planned Behaviour (TPB) was applied as the theoretical framework of the study. Within a qualitative research method four focused group interviews with 30 rural mothers were employed to generate data.FindingsThe stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…A research finding mentioned that mothers' choices toward food for their children were strongly influenced by a certain cultural norm. Habit believed by a mother directly influences the children's nutrition intake and the mother's attitude and behavior control in child feeding practices (Baloch, Jogezai, & Ismail, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A research finding mentioned that mothers' choices toward food for their children were strongly influenced by a certain cultural norm. Habit believed by a mother directly influences the children's nutrition intake and the mother's attitude and behavior control in child feeding practices (Baloch, Jogezai, & Ismail, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, schools need to address parents' reconceptualization of NE as part of their children's learning experiences instead of availing free food as a token to their children's enrolment in schools. Mothers' role remains critical in this regard as they are closely associated with preparing food for their children (Baloch et al, 2020). Schools have to get mothers onboard considering their capacity enhancement for preparing healthy and nutritious food for their children.…”
Section: Discussionmentioning
confidence: 99%
“…Research exploring intentions related to food intake have used Ajzen's (1985) theory of planned behaviour (TPB) (Baloch et al, 2020). Exploring principals' intentions and assuming a favourable influence on NE implementation, as guided by research (e.g.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of cultural norms on child nutrition extend beyond infancy. A previous study found that food-related cultural norms influenced food selection for primary school children, leading to unbalanced diets ( 14 ). Cultural influences on feeding practices that impacted child nutrition were also reported among immigrant communities living in high-income countries (e.g., Australia), which may lead to child health disparities (e.g., high obesity rates) ( 15 ).…”
Section: Introductionmentioning
confidence: 99%